Trees in the religions of early medieval England - Bintley, Michael D. J. (Anglo-Saxon studies, 2015)
Trees were of considerable importance in Anglo-Saxon religion, both Christian and pre-Christian. This book considers various ways in which trees featured in both, and how they helped to mediate the transition between the two. It argues that trees retained certain symbolic characteristics in Anglo-Saxon belief because of their importance to both heathens and Christians, notably the life-sustaining abundance of the earth. Archaeological, historical and textual evidence is used to present a comprehensive picture. Michael D.J. Bintley is Senior Lecturer in Medieval English Literature at Christ Church University, Canterbury